2022
DOI: 10.1039/d2ra02563a
|View full text |Cite
|
Sign up to set email alerts
|

Micro-nano hierarchical pillar array structures prepared on curved surfaces by nanoimprinting using flexible molds from anodic porous alumina and their application to superhydrophobic surfaces

Abstract: Hierarchical pillar array formed on the curved surface by nanoimprinting using a flexible mold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Therefore, we believe that the PDMS stamps fabricated in this study are also applicable to surfaces with various curvatures. 33…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we believe that the PDMS stamps fabricated in this study are also applicable to surfaces with various curvatures. 33…”
Section: Resultsmentioning
confidence: 99%
“…In our previous report, we showed that optimization of the diameter of nanopillars and interpillar distances could generate surfaces that exhibit superhydrophobic properties exceeding 150° . We also reported that the formation of micro-/nanohierarchical structures by combining micrometer-scale structures in the nanopillar array structures could generate superhydrophobic surfaces with a contact angle of over 170°. ,, However, in our previous studies, the tip shape of polymer nanopillars was limited to a hemispherical shape corresponding to the pore shape of anodic porous alumina, and the effect of the nanopillar tip shape on water- and oil-repellent properties has not yet been investigated. Although there have been many reports on the fabrication of nanopillar arrays using anodic porous alumina as a template, there have been no reports on the control of the tip shape.…”
Section: Introductionmentioning
confidence: 99%
“…Surfaces with fine patterns formed with hydrophobic or oleophobic materials exhibit higher water- and oil-repellent properties than smooth surfaces of the same materials. Liquid-repellent surfaces based on fine patterns have attracted considerable attention because of their potential for various applications such as self-cleaning, anti-biofouling, and antifogging surfaces. It has been reported that nanostructured surfaces fabricated by various methods, such as sol–gel methods, hydrothermal syntheses, and chemical vapor deposition (CVD) methods, can function as hydrophobic surfaces. In the case of oil with lower surface tension than water, it is not easy to form oil-repellent surfaces on the basis of fine patterns, but it has been reported that inverse tapered or overhanging pillar array structures can be used to form oil-repellent surfaces. Since the water- and oil-repellent properties based on the surface fine structures strongly depend on the surface geometry, precise control of surface structures is important to optimize surface wettability. We have reported the formation of polymer nanopillar arrays by nanoimprinting using anodic porous alumina as a mold and their application to superhydrophobic surfaces. Anodic porous alumina is a nanohole array material obtained by the anodization of Al in an acidic electrolyte. When anodized under appropriate conditions, anodic porous alumina with an ordered arrangement of pores of uniform size and shape can be fabricated .…”
Section: Introductionmentioning
confidence: 99%
“…[8] Organisms can adapt to their environment and respond to certain stimuli such as temperature and humidity, thereby regulating their surface wetting behavior. [9] Inspired by biology, people have designed and fabricated various biomimetic surface patterns, and then adjusted the surface properties through external stimuli. [10] Adjusting the surface micro-nano array structure of the material, such as tilting, bending, etc., can change the original equilibrium force on both sides of the droplet, forming such as Laplace pressure difference and surface free energy gradient, [11] or liquid-air interfacial tension changes.…”
mentioning
confidence: 99%